Eggs of little bitterns show high variation and their size increases with latitude. Issue 1 (1st January 2021) - Stępniewski, J.; Halupka, L.; Czyż, B.
Abstract: Egg size is an important determinant of offspring weight and survival. However, despite extensive research on factors affecting egg dimensions, causes of egg variation are not fully understood. Between 2000 and 2016 we studied a population of little bitterns in western Poland, and examined a total of 529 eggs from 88 clutches. Furthermore, we conducted an extensive literature search for data on clutch and egg size from other populations of the species to test hypotheses explaining the relationships between these variables and latitude. Little bitterns in western Poland laid big eggs but also produced large clutches compared to most other studied populations of the species. The ratio of largest to smallest egg calculated for egg volume was 1.75 for all studied eggs, and up to 1.35 within clutches, suggesting a huge variation between and within clutches in the studied population. Egg dimensions were highly intercorrelated, but egg size was not related to clutch size in the study population. The comparison of data from different populations of the species revealed that egg volume increased significantly with latitude and was positively correlated with clutch size. These results support the embryonic temperature hypothesis and clutch cooling rates hypothesis, but contradict the optimal egg dimensions hypothesis.